Coenzyme Q10 and soyphosphatidylcholine in EK extender on preservation of Rhode Island Red poultry semen (Journal of Advanced Veterinary and Animal Research, 2015)
The objective of this study was to evaluate the efficacy of EK extender alone or incorporation with CoenzymeQ10 (CoQ10) and/or soyphosphatidylcholine (SPC) in poultry semen and their effects on seminal traits during temporal storage at 4?C for different time intervals (12 h, 24 h, and 36 h). Heterospermic pooled semen samples diluted (1:4) with EK, EK + SPC, EK+ CoQ10 and EK + SPC + CoQ10 extenders separately, preserved and different spermiogram were assessed. Various seminal traits within the same extender differ significantly (p